Transformational Leadership, Organizational Culture, and Knowledge Sharing on Innovation Performance - Alimuddin (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the effects of transformational leadership, organizational culture, and knowledge sharing on innovation performance. Using a quantitative approach with a cross-sectional survey design, data were collected from 200 employees across various industries using a structured questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that transformational leadership and organizational culture have positive and significant effects on innovation performance. In addition, knowledge sharing is found to have the strongest direct influence on innovation performance. The findings also reveal that transformational leadership and organizational culture significantly enhance knowledge sharing, which in turn contributes to improved innovation outcomes. Furthermore, knowledge sharing is proven to mediate the relationships between transformational leadership and innovation performance, as well as between organizational culture and innovation performance. These results highlight the importance of integrating leadership practices, cultural values, and knowledge-sharing mechanisms to foster innovation. This study contributes to the literature by providing a comprehensive model that explains how leadership and organizational factors interact through knowledge sharing to enhance innovation performance. Practically, the findings suggest that organizations should prioritize transformational leadership development, cultivate a supportive organizational culture, and encourage knowledge-sharing practices to achieve sustainable innovation and competitive advantage.